2013
DOI: 10.1016/j.pec.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the transition from cancer patient to survivor: Pilot study results of the Cancer Survivor Telephone Education and Personal Support (C-STEPS) program

Abstract: Objective To develop a feasibility study of a theory-driven telephone counseling program to enhance psychosocial and physical well-being for cancer survivors after treatment. Methods Participants (n = 66) were recruited from two Colorado hospitals with self-administered questionnaires at baseline and two weeks post-intervention. The one group, intervention only design included up to six thematic telephone counseling sessions over three months. Topics included nutrition, physical activity, stress management, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 56 publications
(41 reference statements)
1
66
0
Order By: Relevance
“…For parents who reported continuing to work on their initial goal, several reported achieving success or making progress during their calls. Our study adds to previous research that has found MI to be effective when delivered over the phone (Garrett et al, 2013) and in changing family behaviors (Woo Baidal et al, 2013). MI was successfully implemented during the phone call component of the HOME Plus intervention and participants reported enjoying the calls.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…For parents who reported continuing to work on their initial goal, several reported achieving success or making progress during their calls. Our study adds to previous research that has found MI to be effective when delivered over the phone (Garrett et al, 2013) and in changing family behaviors (Woo Baidal et al, 2013). MI was successfully implemented during the phone call component of the HOME Plus intervention and participants reported enjoying the calls.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies suggest that MI is effective even by telephone. When cancer survivors received phone calls from trained motivational interviewers regarding a healthy lifestyle, coping and stress management, those who received MI significantly lowered their levels of stress and significantly increased their daily servings of fruits and vegetables compared to those who did not receive MI (Garrett et al, 2013). Furthermore, overweight veterans who participated in a small-change, phone-based weight loss intervention had significant reductions in body mass index (BMI) and waist circumference, and significant increases in their daily intake of fruits and vegetables (Damschroder, Lutes, Goodrich, Gillon, & Lowery, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41] Early interventions designed to promote positive psychological resources have shown promise in adults with cancer, [42][43][44][45][46] healthy AYAs, 47,48 and AYAs undergoing hematopoietic stem cell transplant for malignancy. 49 We have previously shown that self-perceptions of personal resources mediate these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, fear of recurrence after treatments have been completed should be addressed since excessive fear and caution has the potential to impede the transition from cancer patient to cancer survivor, hindering adaptation and personal growth (Garrett et al, 2013). …”
Section: Reframing Thoughts and Imagesmentioning
confidence: 99%